Model Integrasi Pembelajaran PAI di Sekolah dan Pesantren: Studi Kasus pada SMP BP Amanatul Ummah Pacet - Alimuddin Pohan; Ammar Zainuddin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The results of the research that have been researched by the author are: First, the reason for the integration of PAI learning at SMP BP Amanatul Ummah Pacet is to deepen students' understanding of Islamic religious teachings. Therefore, integration of PAI learning with book learning is carried out, such as Fiqh using Mabadiul Fikihiya and Arabic using Akidatul Awam. Obstacles faced include the difficulty of teachers dividing time between PAI and muis as well as the challenges of adapting new grade 7 students from elementary school. Solutions include teacher adaptation to changing moods and student maturity levels as well as developing engaging and effective teaching methods to maintain student focus. Second, the form of integration of learning that uses the Integrated model (The Integrated Model).